199 Mechanical thrombectomy for acute ischaemic stroke – outcomes from Sheffield. Issue 9 (12th August 2022) - Moore, Sophie; Dyde, Richard; Tse, George; Nagaraja, Sanjoy; Endean, Keith; Redgrave, Jessica; Lindert, Ralf; Harkness, Kirsty
Abstract : Introduction: Mechanical thrombectomy is now in routine use for acute ischaemic stroke. This service audit examines outcomes and complications in the Sheffield regional centre. Methods: Data was collected retrospectively for all patients undergoing mechanical thrombectomy at Sheffield Teaching Hospitals from March 2020 – February 2021 using case notes and digital records. The data was analysed for the whole group (n=33), and for the subgroup of patients (n=8) aged over 80. Results: 33 patients, aged 31-87, underwent mechanical thrombectomy. 88% had successful revasculari- sation (TICI grade 2b/3). 48% had a good functional recovery (modified Rankin scale 0-2). 6 patients had haemorrhagic transformation, though none met the SITSMOST criteria for symptomatic intracerebral haemorrhage secondary to procedure. 6 patients (18%) did not survive to 90 days. In the group aged over 80, outcomes were significantly worse. In this group the rate of successful revas- cularisation was 63%, and good functional recovery (mRS 0-2) was 13%. 90 day mortality was 38%. Conclusions: Outcomes from mechanical thrombectomy at Sheffield teaching hospitals are good, with nearly half of patients having a good functional recovery. However, outcomes in the subgroup of patients aged over 80 were significantly poorer, with high complication and mortality rates; this warrants further study.